The first patient treatment of electromagnetic-guided real time adaptive radiotherapy using MLC tracking for lung SABR. Issue 1 (October 2016) - Booth, Jeremy T.; Caillet, Vincent; Hardcastle, Nicholas; O'Brien, Ricky; Szymura, Kathryn; Crasta, Charlene; Harris, Benjamin; Haddad, Carol; Eade, Thomas; Keall, Paul J.
Abstract: Background and purpose: Real time adaptive radiotherapy that enables smaller irradiated volumes may reduce pulmonary toxicity. We report on the first patient treatment of electromagnetic-guided real time adaptive radiotherapy delivered with MLC tracking for lung stereotactic ablative body radiotherapy. Materials and methods: A clinical trial was developed to investigate the safety and feasibility of MLC tracking in lung. The first patient was an 80-year old man with a single left lower lobe lung metastasis to be treated with SABR to 48 Gy in 4 fractions. In–house software was integrated with a standard linear accelerator to adapt the treatment beam shape and position based on electromagnetic transponders implanted in the lung. MLC tracking plans were compared against standard ITV-based treatment planning. MLC tracking plan delivery was reconstructed in the patient to confirm safe delivery. Results: Real time adaptive radiotherapy delivered with MLC tracking compared to standard ITV-based planning reduced the PTV by 41% (18.7–11 cm 3 ) and the mean lung dose by 30% (202–140 cGy), V20 by 35% (2.6–1.5%) and V5 by 9% (8.9–8%). Conclusion: An emerging technology, MLC tracking, has been translated into the clinic and used to treat lung SABR patients for the first time. This milestone represents an important first step for clinical real-time adaptive radiotherapy that could reduce pulmonary toxicity in lung radiotherapy.